The IAB Job Vacancy Survey: design and research potential - Mario Bossler; Nicole Gürtzgen; Alexander Kubis; Benjamin Küfner; Benjamin Lochner (Journal for Labour Market Research, 2020)
This article provides an overview of the IAB Job Vacancy Survey and its research potential. The IAB Job Vacancy Survey is a quarterly establishment survey covering the (un-)satisfied labor demand in Germany. This survey identifies the entire number of vacancies on the German labor market, including those vacancies that are not reported to the Federal Employment Agency. The main questionnaire obtains information about the number and structure of vacancies, future labor demand, the current economic situation and the expected development of participating establishments. In addition, the questionnaire collects information about the last new hiring and the last case of a failed recruitment process. Finally, the questionnaire enquires about employer attitudes and firms' use of current labor market instruments. The Research Data Centre of the German Federal Employment Agency offers access to the data starting from the survey waves 2000 onwards.
Keywords: J23; J6; 330; Vacancies; Labor demand; Recruitment; Job vacancy survey; Establishments